"Aceitar Jesus, porque Satanás atenta..." : as conversões neopentecostais no presídio feminino de Sergipe - Santana, Viviane Rocha de (2013)
This thesis aims to analyze the religious evangelical women´s prison in Sergipe, understand the social conditions peculiar to this context that contribute to a high rate of conversion, and in particular, to analyze the changes in practices - speeches and actions - as a result of conversion in the lives of social actors who engage in the practice criminal offense, which is not always reintroduced the role of ´protagonists´ of their lives, but usually acted as ´adjuncts´ of their own destiny, and today are considered "marginal" a term that may be appropriate in the sense that they were always on the fringes of society, everything that ensures the dignity of the human person. Once arrested, these people seek mechanisms that represent a possible alternative to many uncertainties, suffering, distress. One such alternative may be the religion.